Chairwork in schema therapy for patients with borderline personality disorder—A qualitative study of patients' perceptions - Josek, Anna Katharina; Schaich, Anja; Braakmann, Diana; Assmann, Nele; Jauch-Chara, Kamila; Arntz, Arnoud; Schweiger, Ulrich; Fassbinder, Eva (Frontiers in Psychiatry, 2023)
Abstract Objective: Chairwork is one of the core experiential techniques of Schema Therapy (ST) which is used in the treatment of patients with borderline personality disorder (BPD). However, little is known about how people with BPD experience chairwork. The aim of this study was to explore the experiences of patients with BPD with chairwork in ST. Method: Qualitative data were collected through semi-structured interviews with 29 participants with a primary diagnosis of BPD who experienced chairwork as part of their ST treatment. The interview data were analyzed using qualitative content analysis. Findings: Many participants reported initial skepticism, and difficulties with engaging in chairwork. Specific therapist behaviors as well as some external (e.g. restricted facilities, noise) and internal factors (especially feeling ashamed or ridiculous) were named as hindering factors. Participants described several therapist behaviors facilitating chairwork such as providing safety, clear guidance through the process as well as flexible application of the technique according to their needs, and sufficient time for debriefing. Participants experienced emotional pain and exhaustion as short-term effects of the technique. All participants reported positive long-term effects including an improved understanding of their mode model as well as positive mode changes (e.g., less punitive parent and more healthy adult mode), greater self-acceptance, improvements in coping with emotions and needs as well as improvements in interpersonal relationships. Conclusions: Chairwork is experienced as an emotionally demanding but valuable technique. Based on the participants’ statements, the delivery of chairwork can be optimized which can help to improve treatment outcome.